1991
DOI: 10.1159/000235517
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Mediator Release from Human Glomerular Mesangial Cells by the Terminal Complement Components C5b-9

Abstract: Exposure of cultured human glomerular mesangial cells (GMC) to normal human serum and an activator of the complement system results in rapid uptake of the terminal complement proteins C5b-9 by the cells. This ‘innocent bystander’ complement attack, however, does not result in cell killing, but in the stimulation of the GMC to release prostaglandin E (PGE), interleukin 1 (Il-1) and tumor necrosis factor (TNF). Endogenously synthesized Il-1 in turn activates PGE release, indicating that the C5b-9 attack initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 12 publications
(16 reference statements)
1
29
0
Order By: Relevance
“…In doses ranging from 0.02 to 2 ng/ml/105 GMC, TGFPl did not stimulate a measurable release of TNFa, IL-1 or IL-6 into the cell supernatant, despite the fact that the GMC released these cytokines in response to recornbinant IL-1P. In agreement with the literature, 24 h after addition of IL-Ip, a minor release of TNFa, but a considerable release of IL-1p and IL-6, was seen (data summarized in Table 3) (Schonermark et al, 1991;Zoja et al, 1991).…”
Section: Effect Of Tgfp On Cytokine Releasesupporting
confidence: 88%
“…In doses ranging from 0.02 to 2 ng/ml/105 GMC, TGFPl did not stimulate a measurable release of TNFa, IL-1 or IL-6 into the cell supernatant, despite the fact that the GMC released these cytokines in response to recornbinant IL-1P. In agreement with the literature, 24 h after addition of IL-Ip, a minor release of TNFa, but a considerable release of IL-1p and IL-6, was seen (data summarized in Table 3) (Schonermark et al, 1991;Zoja et al, 1991).…”
Section: Effect Of Tgfp On Cytokine Releasesupporting
confidence: 88%
“…First, MAC has been shown to cause proliferation of glomerular mesangial, endothelial, and epithelial cells in vitro and therefore may be directly involved in inducing a increase in intrinsic cell number (17,21,44,45). Additionally, there are data indicating that MAC can induce the synthesis and/or secretion of a number of proinflammatory cytokines such as TNF-␣ and IL-1 (22,44), adhesion molecules such as ICAM-1 and E selectin (23), and chemokines such as IL-8 (46) and that these effects may play a role in the infiltration of cells to the glomerulus. We have also demonstrated that later in the progression of ANTN, mCd59a deficiency, by allowing unregulated MAC deposition, exacerbates glomerular thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that sublethal MAC can mediate proliferative, proinflammatory and profibrotic effects in vitro in glomerular cells (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). MAC has also been shown to be involved in the pathogenesis of a number of glomerular diseases in vivo, including membranous nephropa-thy (24,25) and immune complex nephritis (26,27).…”
mentioning
confidence: 99%
“…In experimental glomerulonephritis, the membrane attack complex (MAC) frequently plays an important role in causing cell-lysis. [23][24][25][26] In this low-dose model, the influence of MAC is probably milder than in the high-dose model. Neutrophils also play an important role in the induction and progression of nephritis.…”
Section: Discussionmentioning
confidence: 99%